Child health handbook records for monitoring growth and development (Research, Society and Development, 2020)
The research aimed to identify in the publications the records of the Child Health Handbook and analyze its evidence in the context of primary care. An integrative literature review study was carried out, with a search carried out in the VHL, SCIELO, MEDLINE, LILACS and BDENF databases. The descriptors "Child", "Personal Health Records" and "Child Development" were used. A total of 2,668 articles were found from all databases, with the application of the inclusion and exclusion criteria, 698 articles for reading were concluded. Right after reading, 10 articles were finalized for structuring the work. Despite the relevance of the CSC, the results of the present study demonstrate a low rate of completion, as all articles showed a deficit in the quality of the records. Therefore, health education becomes essential, in order to guide health professionals and professionals, aiming at greater knowledge about its importance, incentive regarding its proper use and training to improve the assistance provided to the child.